A novel p53 regulator, C16ORF72/TAPR1, buffers against telomerase inhibition. Issue 4 (4th March 2021) - Benslimane, Yahya; Sánchez‐Osuna, María; Coulombe‐Huntington, Jasmin; Bertomeu, Thierry; Henry, Danielle; Huard, Caroline; Bonneil, Éric; Thibault, Pierre; Tyers, Mike; Harrington, Lea
Abstract: Telomere erosion in cells with insufficient levels of the telomerase reverse transcriptase ( TERT ), contributes to age‐associated tissue dysfunction and senescence, and p53 plays a crucial role in this response. We undertook a genome‐wide CRISPR screen to identify gene deletions that sensitized p53‐positive human cells to telomerase inhibition. We uncovered a previously unannotated gene, C16ORF72, which we term Telomere Attrition and p53 Response 1 ( TAPR1 ), that exhibited a synthetic‐sick relationship with TERT loss. A subsequent genome‐wide CRISPR screen in TAPR1 ‐disrupted cells reciprocally identified TERT as a sensitizing gene deletion. Cells lacking TAPR1 or TERT possessed elevated p53 levels and transcriptional signatures consistent with p53 upregulation. The elevated p53 response in TERT ‐ or TAPR1 ‐deficient cells was exacerbated by treatment with the MDM2 inhibitor and p53 stabilizer nutlin‐3a and coincided with a further reduction in cell fitness. Importantly, the sensitivity to treatment with nutlin‐3a in TERT ‐ or TAPR1 ‐deficient cells was rescued by loss of p53. These data suggest that TAPR1 buffers against the deleterious consequences of telomere erosion or DNA damage by constraining p53. These findings identify C16ORF72/TAPR1 as new regulator at the nexus of telomere integrity and p53 regulation. Abstract : Telomere erosion leads to an upregulation of p53 that ultimately results in cell arrest or death. Via genome‐wide screens, we identified a previously unannotated gene, C16ORF72/TAPR1 (Telomere Attrition and P53 Response 1), that was synthetically sick with telomerase inhibition or TERT loss. TAPR1 deletion led to elevated p53 activation in response to DNA damage or telomere erosion, possibly via its interaction with the E3 ubiquitin ligase, HUWE1.